Controlling Firearms - Kaplan, John (1979)
One may ask why I am beginning a lecture entitled Controlling Firearms with analogies between drugs and alcohol. The reason is simple: I propose to draw an analogy between drugs and firearms. Part of the reason for this is that I have worked in the drug area for over a decade while my interest in guns is much more recent. In addition, the similarities in the way we discourse about drug control and about firearms control are striking. Finally, and most important, the issues with which we grapple in the drug control area may, on examination, turn out to be very similar to those that would concern us if we were to make a serious effort at controlling firearms